Age‐ and sex‐specific normative values of bone mineral density in the adult glenoid. Issue 2 (1st June 2022) - Eghbali, Pezhman; Becce, Fabio; Goetti, Patrick; Vauclair, Frederic; Farron, Alain; Büchler, Philippe; Pioletti, Dominique; Terrier, Alexandre
Abstract: The objective of this study was to determine the normative bone mineral density (BMD) of cortical and trabecular bone regions in the adult glenoid and its dependence on the subject's age and sex. We analyzed computed tomography (CT) scans of 441 shoulders (310 males, 18–69 years) without any signs of glenohumeral joint pathology. Glenoid BMD was automatically quantified in six volumes of interest (VOIs): cortical bone (CO), subchondral cortical plate (SC), subchondral trabecular bone (ST), and three adjacent layers of trabecular bone (T1, T2, and T3). BMD was measured in Hounsfield unit (HU). We evaluated the association between glenoid BMD and sex and age with the Student's t test and Pearson's correlation coefficient ( r ), respectively. The lambda‐mu‐sigma method was used to determine age‐ and sex‐specific normative values of glenoid BMD in cortical (CO and SC) and trabecular (ST, T1, T2, and T3) bone. Glenoid BMD was higher in males than females, in most age groups and most VOIs. Before 40 years old, the effect of age on BMD was very weak in both males and females. After 40 years old, BMD declined over time in all VOIs. This BMD decline with age was greater in females (cortical: r  = −0.45, trabecular: r  = −0.41) than in males (cortical: r  = −0.30; trabecular: r  = −0.32). These normative glenoid BMD values could prove clinically relevant in the diagnosis and management of patients with various shoulder disorders, in particular glenohumeral osteoarthritis and shoulder arthroplasty or shoulder instability, as well as in related research.